Histological Alterations in Some Organs of African Catfish (Clarias gariepinus) Exposed to Sub-lethal Concentrations of Glyphosate [N-(phosphonomethyl) glycine] - Akinbadewa, Adedamola; Adewole, Henry; Adeyeni, Stephen; Olaleye, Victor (Borneo Journal of Resource Science and Technology, 2021)
This study used a static bioassay to investigate the histological effects of glyphosate on the gill, liver and muscle of African catfish (Clarias gariepinus) fingerlings. This was done with a view of further characterising the effect of glyphosate on C. gariepinus fingerlings and other aquatic life forms. Six-week old C. gariepinus fingerlings with an average weight of 10.02 ± 0.2 g were stocked into three exposure sets (control, 2.75 ppm (25% of the 96 h LC50 value) and 5.50 ppm (50% of the 96 h LC50 value)) in triplicate at 30 fish per tank for 70 days. The 96 h LC50 value was 11.00 mg/L. Histological examination of the C. gariepinus exposed to various sublethal concentrations of glyphosate showed that major histological changes in their organs were concentration dependent such as gill arch vacuolation, excessive mucosal secretions, lifting of epithelial, and epithelium thickening, hyperplasia and telangiectasis in the gills, discolouration, change in form and consistent alterations involving hyperplasia, narrowing of the central nerve, necrosis, pkynosis, blood congestion and vacuolation of the liver, mild hyperplasia and inflammatory responses in the muscle of the fish. The severity of histological alteration was more pronounced in fish organs exposed to 5.50 ppm of glyphosate concentration. This study concluded that the toxicant (glyphosate) is highly toxic to C. gariepinus particularly at a concentration of 5.50 ppm, therefore its use near farm lands or adjacent water bodies should be discouraged.